2019
DOI: 10.34172/jcvtr.2020.05
|View full text |Cite
|
Sign up to set email alerts
|

Association between dietary inflammatory index and components of metabolic syndrome

Abstract: Introduction: Limited data are available on the association of Dietary Inflammatory Index (DII) with metabolic syndrome (MetS) and its components. The present study was conducted to investigate the association of DII with MetS and its components among Iranian adults. <br /> Methods: A total of 404 subjects, aged 18 years or older, were included in the current cross-sectional study. We used a validated and reliable 147-item food frequency questionnaire (FFQ) to assess dietary intakes. Fasting blood sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…Our findings on the association of E-DII scores with MetS and/or cardiometabolic risk components in Ecuadorian women are consistent with some but not studies that reported on women or stratified their results by sex in non-Latin American populations. For example, our findings on the relationship of E-DII scores with MetS concur with those published on women participants in a South Korean study [ 29 ] but differ from the lack of association reported for other South Korean [ 32 ] or Chinese women [ 30 ]. They also are in agreement with those studies identifying a positive association between E-DII scores and waist size [ 28 , 29 ] or fasting blood triglycerides [ 29 ] in women from Spain and/or South Korea.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Our findings on the association of E-DII scores with MetS and/or cardiometabolic risk components in Ecuadorian women are consistent with some but not studies that reported on women or stratified their results by sex in non-Latin American populations. For example, our findings on the relationship of E-DII scores with MetS concur with those published on women participants in a South Korean study [ 29 ] but differ from the lack of association reported for other South Korean [ 32 ] or Chinese women [ 30 ]. They also are in agreement with those studies identifying a positive association between E-DII scores and waist size [ 28 , 29 ] or fasting blood triglycerides [ 29 ] in women from Spain and/or South Korea.…”
Section: Discussionsupporting
confidence: 55%
“…They also are in agreement with those studies identifying a positive association between E-DII scores and waist size [ 28 , 29 ] or fasting blood triglycerides [ 29 ] in women from Spain and/or South Korea. However, they disagree with the results published on E-DII scores and waist measurements [ 30 , 32 ], BMI [ 28 ], blood triglyceride levels [ 30 , 32 ], blood HDL-c and blood glucose levels [ 29 , 30 , 32 ] in women from countries including Spain, China, Korea and Iran.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…28 On the other hand, some previous studies showed an inverse association between DII and obesity [29][30][31][32] or no association with body weight, BMI, fat mass and abdominal obesity. [10][11][12] These controversies may be partly because of differences in the populations of the studies, metabolic disorders, BMI cut-offs, age, sex and socioeconomic status, dietary supplements, and the number of foods and nutrients included in the DII calculations. It also may be related to reporting biases that are known to vary by weight status.…”
Section: Discussionmentioning
confidence: 99%
“…8 Some studies have shown a direct relationship between the DII with BMI and abdominal obesity in individuals with high cardiovascular risk, 9 while other population-based studies did not observe any association with body weight, BMI, fat mass and abdominal obesity. [10][11][12] Few studies have been conducted to investigate the DII in healthy adults with different BMI status and considering the potential role of age and sex.…”
mentioning
confidence: 99%